Problematika Penentuan Status Keuangan Negara Dalam Badan Usaha Milik Negara Persero - Nelvia Roza (Universitas Islam Indonesia, 2022)
State-Owned Enterprises as one of the economic actors in the national economic system are represented by the director. In carrying out their duties, directors are often faced with the risk of loss experienced by State-Owned Enterprises. The problem that then arises is related to the meaning of state financial status which is included in State-Owned Enterprises. This normative research analyzes the intersection between several laws relating to the meaning of the state's financial status. This study concludes that firstly, the problems regarding the meaning of financial status in state finances occur because of the overlapping of several rules related to the meaning of state financial status which are included in State-Owned Enterprises, especially Law Number 17 of 2013 on State Finance and Law Number 19 of 2013 on State-Owned Enterprises which has a different perspective. Second, that the meaning of state financial status included in State-Owned Enterprises must be understood absolutely as state finances because the meaning of state finances must be understood broadly and comprehensively, so that large amounts of state finances can be saved and used for the greatest welfare of the Indonesian people.Key Words: State-owned enterprises; state financialAbstrakBadan Usaha Milik Negara sebagai salah satu pelaku ekonomi dalam sistem perekonomian nasional diwakili oleh direktur. Dalam menjalankan tugasnya, direktur seringkali dihadapkan dengan resiko kerugian yang dialami oleh Badan Usaha Milik Negara. Permasalahan yang kemudian muncul adalah terkait pemaknaan status keuangan negara yang disertakan dalam Badan Usaha Milik Negara. Penelitian normatif ini menganalisis persinggungan antara beberapa undang-undang yang berkaitan dengan pemaknaan status keuangan negara tersebut. Penelitian ini menyimpulkan, pertama bahwa problematika mengenai pemaknaan status keuangan yang berada di dalam keuangan negara ini terjadi karena adanya tumpang tindih beberapa aturan terkait pemaknaan status keuangan negara yang masuk ke dalam Badan Usaha Milik Negara khususnya Undang-Undang Nomor 17 Tahun 2013 tentang Keuangan Negara dan Undang-Undang Nomor 19 Tahun 2013 tentang Badan Usaha Milik Negara yang mempunyai perspektif berbeda. Kedua, bahwa pemaknaan status keuangan negara yang disertakan dalam Badan Usaha Milik Negara harus dipahami mutlak sebagai keuangan negara karena pemaknaan terhadap keuangan negara harus dipahami secara luas dan komprehensif, agar keuangan negara yang besar jumlahnya dapat diselamatkan dan digunakan untuk sebesar-besarnya kesejahteraan rakyat Indonesia.Kata-kata Kunci: Badan usaha milik negara; keuangan negara